Literature Review: Pengaruh Defisiensi Vitamin D pada Pasien COVID-19 - Theresia Chrisanthy Kustiawan; Siti Rahayu Nadhiroh (Universitas Airlangga, 2023)
Background: Sun exposure contains ultraviolet light is needed by humans in terms of the formation of active vitamin D. The Coronavirus Disease 2019 (COVID-19) pandemic implementing the